2021
DOI: 10.3390/nu13061842
|View full text |Cite
|
Sign up to set email alerts
|

Diet Quality Indices and Physical Activity Levels Associated with Adequacy of Gestational Weight Gain in Pregnant Women with Gestational Diabetes Mellitus

Abstract: The aim of this study was to evaluate the Diet Quality Index (DQI) and the Physical Activity (PA) levels associated with adequacy of gestational weight gain in pregnant women with gestational diabetes mellitus (GDM). A total of 172 pregnant women with a single fetus and a diagnosis of GDM participated. Food intake was self-reported on the food frequency questionnaire and DQI was quantified using the index validated and revised for Brazil (DQI-R). To assess PA, the Pregnancy Physical Activity Questionnaire was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 33 publications
2
5
0
Order By: Relevance
“…Conversely, an association between diet quality and IWG was not observed in our study. Our findings corroborate the effect of dietary assessment tools on EWG from studies conducted in Brazil (Almeida et al, 2021 ), Norway (Hillesund et al, 2014 ) and Sweden (Augustin et al, 2020 ). Regardless of what components the tools consist of, a higher score was always correlated with a better intake of nutrients and good eating habits and food choices (Fransen & Ocké, 2008 ).…”
Section: Discussionsupporting
confidence: 89%
“…Conversely, an association between diet quality and IWG was not observed in our study. Our findings corroborate the effect of dietary assessment tools on EWG from studies conducted in Brazil (Almeida et al, 2021 ), Norway (Hillesund et al, 2014 ) and Sweden (Augustin et al, 2020 ). Regardless of what components the tools consist of, a higher score was always correlated with a better intake of nutrients and good eating habits and food choices (Fransen & Ocké, 2008 ).…”
Section: Discussionsupporting
confidence: 89%
“…We found the weight percentiles by GW could be used to estimate the risk of full-term LBW or macrosomia (OBW) during pregnancy, both LBW and macrosomia were prevalent and associated with increased risks of perinatal morbidity and mortality [24][25][26][27][28].This study showed more frequency of maternal weight under 10th percentile during pregnancy was higher risk of LBW and lower risk of OBW, in contrast more frequency of maternal weight over 90th percentile during pregnancy was lower risk of LBW and higher risk of OBW, but we didn't nd similar report. Many previous reported that inappropriate amount or rate of GWG were associated with adverse pregnancy outcomes including LBW and macrosomia [2,29,30], and low or excess pre-pregnancy BMI, gestational diabetes mellitus, and maternal anemia also increased the risk of LBW or macrosomia [31][32][33][34][35][36][37], this paper also showed these factors were associated with LBW or OBW. Furthermore, maternal age, abnormal reproductive history, assisted reproductive, scarred uterus, parity, delivery mode, and infant sex were considered determinant factors of LBW or OBW, which were consistent with the previous reports [38 -42].…”
Section: Discussionmentioning
confidence: 54%
“…In Japan, the Japan Society of Obstetrics and Gynecology guidelines on gestational weight gain (created in 1995) have historically been strict (9–12 kg gain for women with BMI < 18.5 kg/m 2 ), and prevention of PE has been a high priority for obstetricians in Japan 11 . Although this study did not focus on obstetrical outcomes such as cesarean section, complicated deliveries, fetal acidosis, birth of large‐for‐gestational‐age infants, gestational diabetes mellitus, and postpartum depression, 11–13,30 which are affected by excessive gestational weight gain, the present study still provides new evidence that weight gain of 13.0 kg during pregnancy should be the upper limit among underweight women to reduce PE risk.…”
Section: Discussionmentioning
confidence: 97%